Biorational control programme for the German cockroach (Blattaria: Blattellidae) in selected urban communities. - Shahraki, Gholam Hossein; Ibrahim, Yusof; Mohd Noor, Hafidzi; Rafinejad, Javad; Shahar, Mohd Khadri (Malaysian Society of Parasitology and Tropical Medicine, 2010)
This study assessed the effectiveness of a biorational control approach using 2% hydramethylnon gel bait on German cockroaches, Blattella germanica (L.) in some residential and hospital buildings in South Western Iran. In total, three buildings consisting of 150 apartment units and 101 hospital units were monitored weekly via sticky trap for German cockroach infestations over a period of eight months. These infested units were randomly subjected to intervention and control treatments. Pamphlets and posters were provided and lectures were given to support the educational programmes as a tactic of the biorational system. Survey on cockroach index for intervention units showed 67-94% recovery to achieve clean level of infestation for intervention units of the residential buildings and 83% for the hospital. Mean percentage reductions for treatment groups throughout the 15-week treatment period were 76.8% for the residential buildings and 88.1% for the hospital, showing significant differences compared to the control groups. Linear regression of infestation rates were recorded weekly after treatment and their negative slope for treatment groups substantiated significant reductions for interventions. The results of this study showed that biorational control method, using gel bait, educational programmes and sanitation, is an effective way to manage German cockroach infestation.